Index to Proceedings of the General Assembly 2021/2022 - United Nations Department of Global Communications (United Nations, 2023)
The Index to Proceedings of the General Assembly is a bibliographic guide to the proceedings and documentation of the General Assembly. This issue covers the seventy-sixth session of the Assembly including its Main and ad hoc committees. The Index is prepared by the Dag Hammarskjöld Library, Department of Global Communications, as one of the products of the United Nations Bibliographic Information System (UNBIS).